2017
DOI: 10.1161/jaha.117.005838
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Biology Approach to Investigating Sex Differences in Cardiac Hypertrophy

Abstract: BackgroundHeart failure preceded by hypertrophy is a leading cause of death, and sex differences in hypertrophy are well known, although the basis for these sex differences is poorly understood.Methods and ResultsThis study used a systems biology approach to investigate mechanisms underlying sex differences in cardiac hypertrophy. Male and female mice were treated for 2 and 3 weeks with angiotensin II to induce hypertrophy. Sex differences in cardiac hypertrophy were apparent after 3 weeks of treatment. RNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
2
9
0
Order By: Relevance
“…Maladaptive remodeling following MI encompasses three prominent closely linked and co-dependent progressive processes: hypertrophy, inflammation and fibrosis. Human data from hypertrophied (non-ischemic) patients, experimental hypertrophy models and recent systems biology approaches revealed gender-specific alterations in LV hypertrophy, pro-inflammatory and pro-fibrotic gene expression and collagen deposition ( 72 74 ). These findings combined with conflicting observations regarding the effects of steroids on risk for or outcome post-MI imply the necessity to further elicit gender-differences in the type and extent of the different remodeling sub-processes.…”
Section: Introductionmentioning
confidence: 99%
“…Maladaptive remodeling following MI encompasses three prominent closely linked and co-dependent progressive processes: hypertrophy, inflammation and fibrosis. Human data from hypertrophied (non-ischemic) patients, experimental hypertrophy models and recent systems biology approaches revealed gender-specific alterations in LV hypertrophy, pro-inflammatory and pro-fibrotic gene expression and collagen deposition ( 72 74 ). These findings combined with conflicting observations regarding the effects of steroids on risk for or outcome post-MI imply the necessity to further elicit gender-differences in the type and extent of the different remodeling sub-processes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] A recent integrative systems biology study showed that the miRNA‐mRNA network also plays an important role for gender differences in cardiac hypertrophy. [ 27 ] The genes with large PC loadings in this identified pathway include PPP3R1 , STAT3 , and TGFB1 , which regulate miRNA hsa‐mir‐133b, hsa‐mir‐21, and MIR29A. In Figure , we grouped subjects by median PC1 values for each sex.…”
Section: Resultsmentioning
confidence: 99%
“…However, transcriptomic analysis has yet to be analyzed in a sex‐specific manner, let alone in a TNNC1 model (Green et al, 2016; Vakrou et al, 2018). A previous study utilizing a systems biology approach investigating the sex differences in mice after angiotensin II‐induced hypertrophy found that inhibition of PPARα by a PPARα inhibitor blocked the sex differences in the development of cardiac hypertrophy (Harrington et al, 2017). Below we discuss some key findings for the transcriptomic analysis of our HCM mouse model that may explain the sexual dimorphic phenotype observed in the echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our physiological results in mice of different sexes, we wanted to determine whether some effects of a specific mutation in cTnC that cause HCM may actually be exacerbated in women. Several RNA‐sequencing based studies implicate genetic modifiers (Christodoulou et al, 2014) or mRNA networks that may play a role in disease expression between the sexes (Harrington et al, 2017). Gaining a better understanding of how this dimorphism is altered in cardiomyopathies of differing etiologies may provide evidence of specific networks of genes that are impacted.…”
Section: Introductionmentioning
confidence: 99%